Pemberdayaan Keluarga dan Kader Dalam Pencegahan Anemia Ibu Hamil di Taliabu - Dianita Widya Gandhi; Bima Suryantara; Evy Ernawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Anemia among pregnant women remains a major public health problem that contributes to an increased risk of pregnancy and childbirth complications, particularly in island regions and areas with limited access to health services such as Taliabu Island. Low levels of knowledge among families, limited capacity of health cadres, and minimal involvement of community leaders hinder optimal efforts to prevent anemia. This community service program aimed to improve maternal health by empowering families, health cadres, and community leaders in the prevention of anemia among pregnant women. A participatory community empowerment approach was employed through health education, cadre training, field mentoring, and the use of contextual educational media in the form of leaflets and modules. Program evaluation was conducted using pre-test and post-test methods to assess changes in participants’ knowledge, attitudes, and behaviors. The results demonstrated an increase in participants’ knowledge by more than 30% following the intervention, enhanced capacity of health cadres to deliver health education, and initial positive behavioral changes, including improved adherence to iron supplementation and increased utilization of locally available nutritious food sources. In addition, the program produced educational media registered as Intellectual Property Rights. The empowerment of families and health cadres plays a crucial role in establishing a sustainable community support system for the prevention of anemia among pregnant women.